Nanostructured Lipid Carrier Co-Loaded with Docetaxel and Magnetic Nanoparticles: Physicochemical Characterization and In Vitro Evaluation - Auni Hamimi, Idris; Che Azurahanim, Che Abdullah; Nor Azah, Yusof; Azren Aida, Asmawi; Mohd Basyaruddin, Abdul Rahman (MDPI, 2023)
Lung cancer is currently the most prevalent cause of cancer mortality due to late diagnosis and lack of curative therapies. Docetaxel (Dtx) is clinically proven as effective, but poor aqueous solubility and non-selective cytotoxicity limit its therapeutic efficacy. In this work, a nanostructured lipid carrier (NLC) loaded with iron oxide nanoparticles (IONP) and Dtx (Dtx-MNLC) was developed as a potential theranostic agent for lung cancer treatment. The amount of IONP and Dtx loaded into the Dtx-MNLC was quantified using Inductively Coupled Plasma Optical Emission Spectroscopy and high-performance liquid chromatography. Dtx-MNLC was then subjected to an assessment of physicochemical characteristics, in vitro drug release, and cytotoxicity. Dtx loading percentage was determined at 3.98 w/w, and 0.36 mg/mL IONP was loaded into the Dtx-MNLC. The formulation showed a biphasic drug release in a simulated cancer cell microenvironment, where 40 of Dtx was released for the first 6 h, and 80 cumulative release was achieved after 48 h. Dtx-MNLC exhibited higher cytotoxicity to A549 cells than MRC5 in a dose-dependent manner. Furthermore, the toxicity of Dtx-MNLC to MRC5 was lower than the commercial formulation. In conclusion, Dtx-MNLC shows the efficacy to inhibit lung cancer cell growth, yet it reduced toxicity on healthy lung cells and is potentially capable as a theranostic agent for lung cancer treatment.